Pengembangan Service Excellent pada Edu-Wisata Pesantren Global Cahaya Nubuwah Insani Purwakarta - Pratomo, Luki Adiati; Mariyanti, Tatik; Chandra, Kris; Listiawati, Listiawati; Rahmawati, Ulfi Naria; Anggraeni, Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The Islamic Entrepreneurship Boarding School Purwakarta Global Cahaya Nubuwah Insani (GCNI) integrates religious and entrepreneurship education to develop young santripreneurs. GCNI operates edu-tourism units, including accommodation and a coffee shop, managed by teachers and students. However, observations indicated that students’ service quality remained low due to limited understanding of service marketing and service characteristics. This community service program aims to enhance students’, teachers’, and administrators’ knowledge and skills regarding service concepts, service characteristics, and excellent service practices through training, discussions, and role-playing. The methods consisted of pre-tests, service marketing training, group discussions, and service encounter simulations. The activity results indicated that participants' understanding improved, with 80% demonstrating enhanced service skills, as observed in role, such as friendlier communication, quicker responses, and more accurate information delivery. The program also helped administrators develop more effective marketing strategies for GCNI’s education tourism units. This activity contributes to improving service quality, preparing students to become entrepreneurs, and strengthening the institution’s capacity to manage service-based businesses.